Virtual and augmented reality for the cultural accessibility of people with autism spectrum disorders: A pilot study - Giaconi, Catia; Ascenzi, Anna; Del Bianco, Noemi; D’Angelo, Ilaria; Capellini, Simone Aparecida [UNESP] (Common Ground Research Networks, 2021)
The principles of universal design are the epistemological assumptions of this piece of research. In line with this framework, we explore the potential of new technologies, specifically virtual and augmented reality, in support of inclusive practices in museums. Co-planning actions with people with an autism spectrum disorder have been implemented to increase the participation of all toward culture and heritage. In particular, a multidisciplinary research group has carried out a pilot study with high-functioning university students with autism spectrum disorder. Unpredictable and chaotic contexts have been redesigned—in terms of anticipation and predictability—due to the active support of the students who participated in this study. Specifically, a technological prototype was developed for the creation of an accessible virtual museum tour. In conclusion, the design of accessible spaces has offered the possibility of reaching important benefits in terms of improving the empowerment of people with disabilities and the cultural rights of the whole community.
Keywords: Accessibility; Autism Spectrum Disorder; Cultural Rights; Museums; Technology